Preferred Image of Women on Indian Television: A Move from Classic Stereotypes. Issue 1 (June 2018) - Sandhu, Namrata
This article seeks to suggest that televised portrayals of women should do justice to the evolving image of the present-day woman in India. Such portrayals will not only address the expectations of the audience but also serve desirable social (towards gender equity) and commercial ends.